Dating Methods of Pleistocene Deposits and Their Problems: VII. Paleosols - Evans, L. (Geoscience Canada, 1982)
Summary Paleosols, particularly buried paleosols, have proved valuable stratigraphie markers in many Quaternary studies. They are most commonly found buried by loess in central Europe and the United States, and by volcanic ash in the Pacific margins. Within their morphologies are recorded evidence of past climates and vegetations. The understanding of paleosols has paralleled our comprehension of contemporary soils and hence the methods of investigation of paleosols are those that have found common usage in the study of the soils of today. The recognition of paleosols is thus largely based on the identification of characteristics known in contemporary soils. The usefulness of paleosols as stratigraphic indicators is in part due to their extensive and recognisable occurrence over large areas and because they often contain material suitable for absolute dating by the 14C method. Wood, charcoal, peat and soil organic matter have all been employed in the dating of paleosols. 14C dating of secondary carbonates or oxalates and of plant opal phytoliths, whilst more difficult than the dating of wood, etc., are also possibilities for the Quaternary paleopedologist. Relative dating techniques, particularly changes in the composition of organic matter after burial, have also proved useful in some studies. The reconstruction of paleo environments from paleosol morphology presents many problems and conclusions must be derived from as many lines of evidence as possible. Pollen, opal phytoliths, faunal remains, micro morphology and mineralogical composition should all be investigated and the results integrated to provide a consistent picture of past climates and vegetations. A lack of understanding of pedology can often lead to erroneous conclusions.